Effects of Aflatoxin on Liver and Protective Effectiveness of Esterified Glucomannan in Merino Rams - Fatma Colakoglu; Hasan Hüseyin Donmez (The Scientific World Journal)
The effects of total aflatoxin (AF) given orally on liver in Merino rams were studied. In addition, this study was conducted in order to evaluate the efficacy of an esterified glucomannan (EG) for protection against aflatoxicosis. One-year-old 32 Merino rams were divided into four equal groups. The control group (C) was fed with the commercial feed. The AF group was fed with commercial feed plus 250 μg/day of total AF. The EG group was fed with commercial feed plus 2 g/day of EG. The AF + EG group was fed with commercial feed plus 250 μg/day of total AF and 2 g/day of EG. After feeding period, tissue samples were taken from the liver in order to perform histological analyses. Vacuolar degeneration with small and large droplets and hydropic degeneration in hepatocytes were observed in the AF group. The ceroid pigmentation was observed in macrophages in groups or one by one. It was observed that the fat rate in hepatocytes was 2.6% in the C group, 35.5% in the AF group, 2.9% in the EG group, and 9.6% in the AF + EG group. In conclusion, the adverse effects caused by aflatoxicosis on the liver could be ameliorated by adding EG to the ration.